Auditoría de gestión y su incidencia en los procesos de colocación de productos crediticios de la cooperativa de ahorro y crédito San Antonio Ltda. agencia del cantón Vinces año 2017-2018 - Medrano Suárez, Gabriela Lucila (2019)
The research was based on the importance of the Management Audit within the Cooperative Saving and Credit Saint Antony Ltda. Vinces agency where the objective was to carry out an objective, systematic and professional examination of evidences, which ended by providing an independent evaluation on the performance of collaborators, operational processes that are carried out within the same, with a focus on improving the effectiveness, efficiency and economy in the use of resources. The development of the study raised the existing problem in this institution where deficiencies and weaknesses were evident in the processes of loan placement and collection efforts, activities that were occurring due to the noncompliance with the internal procedures linked to the institution, and the inadequate application of credit policies and regulations that hampered the execution of activities specific to the credit area, which caused a high rate of delinquency that had repercussions on profitability and availability of resources to expand its credit portfolio. Among the objectives pursued by the investigation responded to the performance of a management audit to demonstrate operational procedures in the management of credit products that are offered to partners, these products had a direct relationship with processes of credit placement, as well as the collection management, and extrajudicial processes that entail the non cancellation of a loan and its punishment. Suggested measures to improve collection efforts and reduce the high delinquency as well as greatly diversify the loan portfolio, as well as encourage the growth of the same. Key words: Audit, Credits, Collection, Management, Clients, Effectiveness and Processes.